Consumo de alimentos ultra procesados y su relación con el riesgo cardio metabólico en adolescentes de la Unidad Educativa San Pedro Cantón Guaranda. Bolívar noviembre 2023-abril 2024. - Azogue Chugchilan, Lourdes Umbelina (2024)
Having an adequate diet during adolescence is crucial. Therefore, it is essential that the diet has optimal nutritional value to cover the caloric needs of the adolescent. For this reason, this study aims to determine the relationship between the consumption of ultra-processed foods and cardiometabolic risk in adolescents from the San Pedro Educational Unit, Guaranda-Bolívar canton. November 2023 - April 2024. The methodology applied is through the inductive and deductive method with a descriptive nature, its sample is comprised of 176 adolescents belonging to the San Pedro de Guanujo Educational Unit; As a technique, a survey is applied where data on anthropometric measurements and the frequency of ultra-processed foods consumed by students are collected. RESULTS: 28% of students with high cardiometabolic risk consume mostly 2 to 4 times a week, cookies 18%, snacks 18%, drinks 18%, sweets 17%, sausages 19% and other ultra-processed foods 23%. while 72% of those students with low risk consume mostly 2 to 4 times a week, cookies 37%, snacks 38%, drinks 44%, sweets 38%, sausages 23% and others 41%, CONCLUSION: According to the relationship between cardiometabolic risk and the consumption of ultra-processed foods, those students who consume ultra-processed foods once a week have a high cardiometabolic risk of 9.1%; 2-4 times a week 23.6%; 5-6 times a week 58.1%. While those students who consume ultra-processed foods once a week have a low cardiometabolic risk of 90.9%; 2-4 times a week 76.4% and 5-6 times a week 41.9%.